Kesalehan Artifisial Dan Kesombongan Spiritual Dalam Pengkhotbah 7:16 Serta Implikasinya Terhadap Praktik Keagamaan Jemaat Gereja Masehi Advent Hari Ketujuh Taman Harapan Seretan Timu - Karwur, Hendrik Ayub; Pane, Exson (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study explores the theological and practical meaning of the statement "Do not be overly righteous" in Ecclesiastes 7:16—an admonition often viewed as paradoxical within biblical wisdom literature. The research focuses on exegetical analysis of the original Hebrew text, historical-literary context of the Book of Ecclesiastes, and its implications for the understanding of righteousness within the context of the Seventh-day Adventist Church at Taman Harapan Seretan Timu. The research uses a qualitative approach through literature study and textual analysis. The methods include exegetical analysis of biblical texts, linguistic evaluation of key Hebrew terms, historical-critical interpretation, and contextual theological reflection to identify the relevance of the verse in modern Christian life and spirituality. The findings reveal that the phrase "overly righteous" in Ecclesiastes 7:16 does not reject genuine righteousness but rather criticizes artificial, legalistic, and self-righteous religiosity. The author of Ecclesiastes (Qoheleth) warns against religious extremism and spiritual arrogance, which can be self-destructive both psychologically and spiritually. In the Adventist tradition, these insights affirm the necessity of balanced spirituality—avoiding both legalism and spiritual complacency. This study recommends that Christians, particularly within the SDAC, cultivate authentic and reflective righteousness rooted in grace and a living relationship with God. Such understanding enriches practical theology and supports the development of a contextual, inclusive, and relevant spiritual life in today’s world..